Driver acceptance of partial automation after a brief exposure. (January 2020) - Reagan, Ian J.; Cicchino, Jessica B.; Kidd, David G.
Highlights: Acceptance of five Level 2 systems varied across test vehicles. Adaptive cruise control was trusted more than lane centering. Functional attributes predicted agreement that automation improved driving experience. Uncomfortable experiences with automation occurred in common road scenarios. Abstract: Driving automation systems are being introduced into mass-market vehicles, but little is known about whether drivers will trust driving automation systems and use the technology. In this study, volunteer drivers operated five vehicles equipped with automated longitudinal and lateral control and completed surveys about their experience. A subset of drivers also documented uncomfortable experiences as they used the automation while driving. Driver agreement that the automation improved the overall driving experience was significantly higher for Vehicle A than the systems implemented in the other four vehicles. Drivers reported significantly higher trust in adaptive cruise control than in lane centering in every vehicle but Vehicle B. Increased agreement that the automation consistently detected lane lines; detected moving vehicles ahead; and made smooth, gentle steering inputs was associated with significant increases in agreement that the automation improved the overall driving experience. Situations where drivers reported feeling uncomfortable with the automation during their drive were dominated by instances where lane centering struggled with common roadway features such as hills and intersections.